COMPARATIVE SEMASIOLOGY: SEMANTIC ANALYSIS OF COLOR TERMS IN UZBEK AND ENGLISH - Kholmamatova Risolat (Bright Mind Publishing, 2025)
This article presents a comparative semasiological analysis of color terms in Uzbek and English. The study explores how color terms function semantically within each language, highlighting similarities and differences in cultural, psychological, and linguistic associations. The research uses both qualitative and quantitative methods, analyzing a corpus of texts, dictionaries, and native speaker input. The paper finds that while some basic color terms overlap in meaning and usage, there are significant differences shaped by cultural worldview and traditional symbolism. These findings contribute to a deeper understanding of cross-linguistic semantics and aid translators, linguists, and intercultural communicators.
Keywords: Semasiology, Color Terms, Semantics, Uzbek Language, English Language, Cultural Symbolism, Comparative Linguistics.